THE SENSORYCHARACTERISTICS AND AMINO ACID PROFILE OF REBON SHRIMPSILAGE (Aceteserythraeus) WITH ADDING DIFFERENT AMOUNT OF SAGO FLOUR - Daffa Ramadhan; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTSilage is a liquid product produced from whole fish or the by-product of the fishery processing industry, the liquid phase is caused by enzyme activity in the fish body by adding acids or certain microbes. The carbohydrate content in fresh rebon shrimp was low, that can be added sago flour as a source of carbohydrates. This study aimed to determine the sensory characteristics and amino acid profile of rebon shrimp silage with the addition of different amounts of sago flour. The method used in this research was descriptive method, namely conducting to produce rebon shrimp (Acetes erythraeus) silage using 10% L. plantarum bacteria of the weight of rebon shrimp used. The treatment used was the addition of different amounts of sago flour of which consisted of 4 treatment levels, each: P1 (10%), P2 (20%), P3 (30%), and P4 (40%). The best treatment was P4 with the sensory characteristics of rebon shrimpsilage withblackish brown color, viscous liquid, and the typical acid smell of shrimp. The amino acid consisted of 9 types of essential amino acids and 8 types of non-essential amino acids, with the highest value being glutamic acid as much as 1,956%.Keywords: Amino Acid, Rebon Shrimp, Sago Flour, Sensory, Silage.